2013
DOI: 10.1093/aob/mct111
|View full text |Cite
|
Sign up to set email alerts
|

Floral ontogeny and gene protein localization rules out euanthial interpretation of reproductive units in Lepironia (Cyperaceae, Mapanioideae, Chrysitricheae)

Abstract: Results support the synanthial hypothesis as the evolutionary origin of the reproductive unit. Thus, the basic reproductive unit in Lepironia is an extremely condensed pseudanthium, of staminate flowers surrounding a central terminal pistillate female flower. Early in development the reproductive unit becomes enclosed by a split-prophyll, with the whole structure subtended by a bract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Although morphological synapomorphies could be identified for all tribes of the SCC that are recognized here, most of these synapomorphies are homoplasious at the family level. For instance, fertile prophylls have evolved independently in Dulichieae and in the Cariceae + ​Sumatroscirpeae clade, and may also be present in Mapanioideae if spicoids are homologous to the lateral spikelets of Cyperoideae (Goetghebeur, ; Prychid & Bruhl, ). Likewise, unisexual flowers, characteristic of Cariceae and Khaosokieae in the SCC, are seen in several early‐diverged Cyperaceae tribes including Bisboeckelereae, Cryptangieae, Koyamaeae, Sclerieae, and Trilepideae (Goetghebeur, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although morphological synapomorphies could be identified for all tribes of the SCC that are recognized here, most of these synapomorphies are homoplasious at the family level. For instance, fertile prophylls have evolved independently in Dulichieae and in the Cariceae + ​Sumatroscirpeae clade, and may also be present in Mapanioideae if spicoids are homologous to the lateral spikelets of Cyperoideae (Goetghebeur, ; Prychid & Bruhl, ). Likewise, unisexual flowers, characteristic of Cariceae and Khaosokieae in the SCC, are seen in several early‐diverged Cyperaceae tribes including Bisboeckelereae, Cryptangieae, Koyamaeae, Sclerieae, and Trilepideae (Goetghebeur, ).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological classification in Cyperaceae suffers from uncertainty in character homology, especially pertaining to reproductive structures (e.g., Bruhl, 1991; Vrijdaghs et al, 2007; Reutemann et al, 2012). While analyses of floral ontogeny are helping to cut this Gordian knot (Vrijdaghs et al, 2009, 2010; Prychid and Bruhl, 2013), they are most useful in secondary homology assessment, requiring an a priori phylogenetic hypothesis based on independent data, such as those provided by DNA sequences. Goetghebeur (1998) classified Cladium , Rhynchospora , and Arthrostylis as members of Schoeneae on the basis of inflorescence morphology, but our results place the latter two closer to core Cyperoideae (the clade containing Cypereae, Cariceae, and Abildgaardieae) and Cladium as sister to all other Cyperoideae, consistent with Bruhl (1995), Ghamkhar et al (2007), and Jung and Choi (2013).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent of these classifications (Bruhl, 1995;Goetghebeur, 1998) differ in suprageneric groupings into subfamilies and tribes ;whereas Bruhl (1995) recognized 2 subfamilies and 12 tribes, Goetghebeur (1998) recognized 4 subfamilies and 17 tribes. Phylogenetic analyses at the family level (Muasya & al., 1998(Muasya & al., , 2009aSimpson & al., 2007;Jung & Choi, 2013) divided Cyperaceae into two subfamilies: Mapanioideae, characterized by inflorescences consisting of a basic reproductive unit with two prophyll-like structures and subtended by a bract (Prychid & Bruhl, 2013), and Cyperoideae, characterized by inflorescences with at least one (sometimes all) bisexual flowers. These molecular studies identified several monophyletic groups that correspond to previously recognized tribes, especially those of Goetghebeur (1998), whose tribal circumscription is broadly accepted by most authors (i.e., Simpson & al., 2007;Yano & al., 2012;Larridon & al., 2013), with some modifications.…”
Section: Introductionmentioning
confidence: 99%